Microbial-mediated induced resistance: interactive effects for improving crop health - Charpe, Ashwini M.; Aglave, Balaji; Ghosh, Dilip K. (Frontiers in Microbiology, 2025)
Microbial-mediated induced resistance (MMIR) holds great promise for sustainable agriculture, but its context dependency remains a hurdle to overcome before this potential can be realized under field conditions. MMIR is observed during interactions from the fungal biocontrol agent Trichoderma spp., beneficial microbes like arbuscular mycorrhizal fungi (AMFs), and bacterial species like Bacillus spp. and Pseudomonas spp., which are recognized as plant growth-promoting rhizobacteria within their plant host. Events involved in microbial induction of resistance include priming, oxidative burst, deposition of callose, Ca2+ ion influx, activation of transcriptional factors, activation of defense-related genes, secondary metabolite production, and regulation of stomatal activity. A defense signal cascade involves plant pathways such as the Jasmonic acid (JA) and Ethylene (ET) pathway. Reactive oxygen species (ROS) production is also triggered when plants are inoculated with these beneficial microbes. As a result, such plants become immune to future infection by pathogenic microbes. Fungi such as Trichoderma atroviride, T. harzianum, T. longibrachiatum, Arbuscular Mycorhizal Fungi, Mortierella hyaline, Serendipita vermifera, Acrophialophora jodhpurensis, Piriformospora indica, and bacteria Bacillus subtilis, B. amyloliquefaciens, B. atrophaeus, B. cereus, B. megaterium, Paenibacillus alvei, Pseudomonas aeruginosa, P. fluorescens, Streptomyces lydicus, S. pactum, and Paraburkholderia phytofirmans are reported to induce resistance. Work done on this aspect so far indicates that this phenomenon is highly context-dependent and is affected by biotic factors, abiotic factors, and agricultural practices. A sufficient supply of beneficial microbes in the rhizosphere is needed to induce resistance but does not guarantee triggering signal cascades if conditions are not favorable. To reduce the context dependency, it is required to simulate field-like conditions during experimentation. Alternatively, if the context dependency of MMIR is accepted as inevitable, the focus should shift to developing environmentally stable commercial formulations. Compositions of secondary metabolites from beneficial microbes, known to trigger resistance in the lab, might also induce it consistently in the field. This will require more interdisciplinary research and partnership with industries.